Impact of removal of rubber plantations for urbanization on CO2 mitigating capacity by the loss of carbon sink in Kerala state, India - Ambily, K.K.; Ulaganathan, A.; Sathisha, G. C. (Journal of Plantation Crops, 2022)
Mitigating climate change and global warming through carbon sequestration by tree ecosystems is of prime importance since they are cost-effective, environmentally friendly and ecologically sustainable. Urbanization is a part of development, and rubber plantations are usually removed for this purpose, especially in Kerala, the southern state of India. Besides latex, the economic produce, and the associated income, the rubber tree is a fairly good sink for carbon in its biomass, with an average carbon content of 42 per cent and substantial carbon stock in the soil. In the present study, an account of total carbon loss by the removal of rubber plantation for urbanization and developmental activities are given. The present popular clone (RRII 105) existing in major share (85%) of the total rubber cultivation in India accounts for carbon sink loss 57 t ha-1, 57.5 t ha-1, 43.2 t ha-1 for 23 years and 148 t ha-1, 75 t ha-1 and 62.1 t ha-1 for 30 years from biomass, litterfall and sheet rubber respectively. The recent clones RRII 414, RRII 429 and RRII 417 have higher growth rates and higher biomass (44-50 per cent) carbon sink loss compared to the existing popular clone RRII 105. The carbon sink loss in the form of stored carbon in soil is 56.5, with a soil carbon content between 1.2 to 2 per cent. Due to the growth variation in diverse environments with extreme climatic conditions, the clones recorded differences in carbon stock and carbon sink loss. The central region of Kerala showed a higher loss, and a lower loss was in the drought-affected northern region than the southern region. The total carbon sink losses for 23 and 30 years were 214.2 and 341.5 t ha-1, respectively. This study points out that the serious carbon sink loss due to the removal of rubber plantations results in disturbing the self-sustained, carbon-friendly and economically sound perennial rubber ecosystem. Vegetation having higher C-sequestration potential and trees with higher lignin content is essential to increase carbon capture for mitigating the impact of the removal of plantations. From the present study, it is clear that the removal of rubber plantations is affecting the carbon sink loss, thereby the CO2 mitigating capacity, and is a serious matter of concern.